PENGARUH KINERJA DAN KEPEDULIAN MANAJEMEN BANK PEMBANGUNAN DAERAH DI INDONESIA TERHADAP PORSI PENYALURAN KREDIT PENGEMBANGAN SEKTOR UMKM - S. Riauwanto Soerip (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2015)
This study investigates the effect of performance management and care of BPD in Indonesia against the share of SME sector development lending.The loan portfolio BPD in Indonesia is dominated employee loans (consumer) compared with the productive sectors especially the MSME sector.The inequality shows the composition distribution disitermediari very sharp.Though SME sector contribute greatly to the economy of Indonesia.But the “concern” BPD in Indonesia management is less interested in developing SME loans larger portion of consumer credit (employees).This study uses secondary data sources from Financial Statements 26 BPD in Indonesia period 2005-2009 for which data are derived from the website of Bank Indonesia.Cross-section data and time series of data obtained are arranged into panels totaling 130 sets of data.The data of this research is the dependent variable PK (MSME sector credit portion), while the independent variables consist of CAR, NPL, EQI, ROA, LIQRR, LDR, IRISK, SIZE and SHM.Data management factors described by the factor of “concern” managers and owners (EQI and SHM).The model was tested using Hausman equation to obtain the most appropriate model.The results using fixed effects approach to data processing.Methods of data using multiple regression analysis (multiple regression model), while the data processing using statistical program eviews 6. The study found that the factors “concern” the development of the SME sector is still weak, because the portions are relatively much smaller when compared to consumer credit.In addition to a weak level of concern, caring influence too weak manager and owner of the credit portion of the development of SMEs.This is due to liquid assets tend to be directed and invested in the reserve requerment and not optimized for using the development of SMEs.Another finding is that the overall performance of BPD has no effect on the development of SME lending portion, except NPL factors and SIZE bank.NPL showed a negative effect, while SIZE positive effect on bank lending portion of the SME sector development. Thus, this study found and concluded that the performance of BPD in Indonesia in managing assets - liability to the development of the SME sector is not optimal and efficient.The portion of the SME sector has not made backbound loan portfolio, although a major contribution to the Indonesian economy.Inequality composition of the loan portfolio between consumptive portion and the SME sector credit shows that there has been disintermediari on bank performance.Therefore, profits or revenues (achievement) is now obtained the credit market has yet to show real potential, because lounable support fund owned by the BPD in Indonesia is still very large.